(untitled) (AmS-Skrifter, 2020)
A novel pathway for understanding exchange is via what might be termed historical autecology, in particular, trying to assess introductions and invasive insect species in the environments under investigation. Invertebrates can provide very detailed information on this front, as they inevitably accompany any trading or raiding activities, in ships, either in ballast, dunnage or goods, and overland in packing or commodity. Grain was widely shipped to the north from southern Baltic and North Sea ports, and archaeoentomological research in northern Norway and Iceland has demonstrated that exotic pests for these parts of the world, which rely on the warmth of the storerooms for their survival, arrived as part of the exchange process of fish or skins for grain; a range of other species were transported in dunnage and ballast. This paper discusses insect results and mechanisms for insect pest introductions from a range of sites relevant to the Hanseatic trade, including North Atlantic ones, to show the potential of this research and to provide a framework for future research.